Desain Monitoring Daya Photovoltaik Pada PLTS Autotracking 5 KWP - Hutauruk, Sindak; Sianturi, Libianko; Telaumbanua, Maranata (Jurnal Teknologi Elektro, 2024)
The design of a wireless monitoring tool for photovoltaic output power at a 5 KWP autotracking Solar Power Plant at HKBP Nommensen University in Medan was carried out to facilitate monitoring of the power generated by a Solar Power Plant. The power generated by the photovoltaic is displayed on the monitor screen where the measurement of the power generated by the photovoltaic is carried out by the microcontroller by multiplying the output voltage and current of the photovoltaic. The output from the microcontroller is sent somewhere via the wifi network and Android TV Box to be displayed in real time in the form of decimal numbers and graphics on the monitor screen. From the monitor screen, you can see the amount of light received by the photovoltaic, the amount of voltage, instantaneous power, and energy produced by the photovoltaic. The measurement results displayed on the monitoring screen have an error percentage of 2.253 % of the inverter output power. This power monitoring can also be viewed remotely using an Android-based application.